APLIKASI METODE WASPAS UNTUK PEMILIHAN PESTISIDA BAGI TANAMAN PADI DI CIANJUR - Buhori Muslim; Emil Herdiana (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Rice plants in Cianjur Regency are the main types of crops because all of the existing sub-districts have rice fields, so they are famous for Cianjur Rice, which has been cultivated for generations, the rice has a delicious taste and a distinctive smell. One of the problems of rice planting is pest control, where people use pesticides in the market, it turns out that there are very many types in the market with their respective compositions and advantages so that farmers must carefully choose so that the results are as expected. use to be able to complete the decision support system data (DSS) so that the results are obtained in the form of a decision on the selection of certain pesticide products that are most suitable for the Padai plant pest in the Cianjur Regency area, this is obtained from the input of Pesticide data in the market closest to Farmers and the result is of course the growth of rice and grain is good, rice grain income increases.